Examined and positive lymph nodes counts and lymph nodes ratio are associated with survival in major salivary gland cancer. Issue 8 (23rd March 2019) - Elhusseiny, Khaled Mosaad; Abd‐Elhay, Fatma Abd‐Elshahed; Kamel, Mohamed Gomaa; Abd El Hamid Hassan, Heba Hassan; El Tanany, Heba Hussien Muhammad; Hieu, Truong Hong; Tieu, Thuan Minh; Low, Soon Khai; Hou, Vincent; Dibas, Mahmoud; Huy, Nguyen Tien
Abstract: Background: We aimed to investigate the prognostic role of examined (dissected) lymph nodes (ELNs), negative LNs (NLNs), and positive (metastatic) LNs (PLNs) counts and LN ratio (LNR = PLNs/ELNs×100) in patients with major salivary gland cancer (SGC). Methods: Data were retrieved for major SGC patients diagnosed between 1988 and 2011 from Surveillance, Epidemiology, and End Results program. Results: We have included 5446 patients with major SGC. Most patients had parotid gland cancer (84.61%). Patients having >18 ELNs, >4 PLNs, and >33.33% LNR were associated with a worse survival. Moreover, older age, male patients, grade IV, distant stage, unmarried patients, submandibular gland cancer, and received chemotherapy but not received surgery were significantly associated with a worse survival. Conclusions: We demonstrated that patients with >18 ELNs and >4 PLNs counts, and >33.33% LNR were high‐risk group patients. We strongly suggest adding the ELNs and PLNs counts and/or LNR into the current staging system.